Host–guest chemistry for tuning colloidal solubility, self-organization and photoconductivity of inorganic-capped nanocrystals - Bodnarchuk, Maryna I. (Nat Commun, 2015)
Colloidal inorganic nanocrystals (NCs), functionalized with inorganic capping ligands, such as metal chalcogenide complexes (MCCs), have recently emerged as versatile optoelectronic materials. As-prepared, highly charged MCC-capped NCs are dispersible only in highly polar solvents, and lack the ability to form long-range ordered NC superlattices. Here we report a simple and general methodology, based on host–guest coordination of MCC-capped NCs with macrocyclic ethers (crown ethers and cryptands), enabling the solubilization of inorganic-capped NCs in solvents of any polarity and improving the ability to form NC superlattices. The corona of organic molecules can also serve as a convenient knob for the fine adjustment of charge transport and photoconductivity in films of NCs. In particular, high-infrared-photon detectivities of up to 3.3 × 10(11) Jones with a fast response (3 dB cut-off at 3 kHz) at the wavelength of 1,200 nm were obtained with films of PbS/K(3)AsS(4)/decyl-18-crown-6 NCs.